Philosophical Foundations of Education Lessons for India - Bhatt, Siddheshwar Rameshwar (Springer Singapore, 2018)
This book provides a philosophical foundation to the theory and practice of education from the Indian perspective. It is guided by an 'axionoetic' approach to education and therefore it deals with the epistemological foundation and value orientation of education. The author discusses the ontological, epistemological, logical, ethical and axiological bases of education in a holistic and integrated manner. The author maintains that education is a planned, methodical and purposive enhancement of human potentialities as a natural development. This presupposes correct and adequate formulation of the objectives and goals of education as per the needs and aspirations of pupils. Education also equips individuals for a good quality of life. Keeping in view the applied dimension of philosophy, this book analyses practical issues of moral education like character building value-negativism in the context of education. It also deals with issues concerning peace, sustainable development, sustainable judicious consumption etc. which should have a bearing on educational policies and programmes.